Epistemologi Pembebasan Tokoh Firdaus dalam Novel Perempuan di Titik Nol Karya Nawal El-Saadawi: Tinjauan Filsafat Ilmu - Harahap, Maulidya; Rohanda, Rohanda; Kodir, Abdul (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the form and meaning of the epistemology of liberation represented in Nawal el-Saadawi's novel The Woman at Point Zero using a philosophy of science perspective. The main focus of the study is on how literature functions not only as an aesthetic work but also as an epistemological medium that reflects the process of knowledge acquisition and human liberation from oppressive structures. This study uses a qualitative approach with hermeneutic analysis, which is applied through an in-depth interpretation of the novel's text to trace the development of the main character, Firdaus's, consciousness. The research data consists of narrative quotations and dialogues in the novel, which are analysed interpretively to reveal the relationship between life experience, knowledge, and power in the context of a patriarchal society. The results of the study show that the epistemology of liberation in this novel is reflected through the transformation of Firdaus' consciousness from passive knowledge shaped by social norms and male domination to active knowledge born of critical reflection and resistance. This knowledge serves as a means of emancipation, affirming that women's life experiences can be a legitimate epistemic source in constructing truth and self-awareness.